Analisa Selisih Varians Dalam Upaya Pengendalian Biaya Produksi Sedotan Steril Pada PT. ABC Di Mojokerto - Sujarwanti Sujarwanti; Sutini Sutini; Wiratna Wiratna; Diana Zuhroh; Heri Toni (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
PT. ABC is a company engaged in the processing of plastic pellets and various kinds of straws using machine tools to carry out their production. The purpose of this research is to find out how the production cost budget is prepared by PT. ABC and whether it is correct, and also to find out how to control production costs that occur at PT. ABC and is it efficient. This research is a qualitative research. The research data comes from the financial reports of PT. ABC in 2022, namely in the form of a budget and realization of production costs. The research sources used were interviews and literature studies. Based on the results of the analysis, the procedure for preparing the production cost budget at PT. ABC is not yet fully accurate when compared to existing theoretical studies, because there is a difference that results in inaccuracies in the production cost budgeting procedure. To find out how to control the production costs of PT. ABC and whether it is efficient is to analyze the difference in production costs by comparing the budgeted costs with actual costs. If there is a difference, whether profitable or unprofitable but still below the tolerance limit of 5%, it is said to be efficient. Then to find the cause of the discrepancy, an analysis of the difference in the cost of raw materials and direct labor is used which consists of the difference in price/tariff and the difference in quantity/efficiency. Whereas for the analysis of factory overhead costs using the four differences method consisting of budget differences, capacity differences, fixed efficiency differences, and variable efficiency differences. Based on the results of the difference analysis, it is known that between the budget and realisation, there is a profitable difference of Rp. 97,404,768.14 or 11.25% so that overall it can be said that the budget for production costs of PT. ABC is efficient or under control.